SM-GUI: A Grid-Based XML Schema Management GUI - Milan Kang; Karpjoo Jeong; Sang Boem Lim; Dongkwang Kim; Ok-Hwan Byeon (2007 International Conference on Convergence Information Technology (ICCIT 2007), 2007)
In scientific area, new research subjects are continually being raised and constant efforts has been made to get more effective result through variant research method. With the active progress, there is huge amount of data and metadata stored in different data storages in variety of data formats. This makes very difficult to find and reuse results from previous experiment. It is crucial to manage the data efficiently and adapt one study to new one so that can cope with the change of data types and data structure. This paper provides a visual schema management toolkit to manage the data model and the related data easily in both local environment and grid environment.